Hermansky–Pudlak Syndrome a Case Report - Mary Grace; Shameer V K; Akhilesh Akhilesh; Arun P (International Journal of Medical Research and Review, 2015)
We report a case of Hermansky –Pudlak syndrome in a 34 year old lady who was born of non consanguineous marriage The incidence of HPS is highest in Puerto Rico.There are increasing reports of HPS among Indians. There are only rare case reports where the mode of inheritance is not autosomal recessive.